Inclusive Democracy in Practice: Fulfilling the Political Rights of Persons with Disabilities in the Malang City Election - Wahyudi , Diki; Firdiansyah, Muhammad Ardi (Pencerah, 2025)
This research analyzes the efforts to fulfill the political rights of persons with disabilities in the Malang City election. Persons with disabilities, who may face physical, intellectual, or mental limitations, often encounter barriers in exercising their political rights, even though they are entitled to equal participation in democratic processes. The study aims to evaluate how election stakeholders in Malang City ensure inclusivity in political participation for this marginalized group. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation, and analyzed with the interactive model of Miles and Huberman. The findings reveal that the General Election Commission (KPU) of Malang City has implemented several measures to strengthen participation. First, policies were designed and implemented in accordance with existing regulations to guarantee accessibility. Second, socialization activities were conducted to inform persons with disabilities about election procedures, schedules, and mechanisms. Third, the Election Supervisory Body (Bawaslu) provided oversight to ensure compliance and prevent discriminatory practices. Finally, the Malang Inclusion Forum facilitated regular hearings with the KPU every three months to address specific needs and challenges. In conclusion, the combined efforts of policy implementation, targeted socialization, supervision, and stakeholder collaboration have significantly contributed to the fulfillment of political rights for persons with disabilities in Malang City elections, though continuous improvement is still required to ensure full inclusivity.